The Davao Regional Workshop - Siongco, Celerina M.
The workshop provided more opportunities for the many delegates to acquire more knowledge and better insight into the techniques and nature of group dynamics. Experiences in these methods are very essential to classroom leadership. Teachers know how to describe this group process but very few actually practice it in classrooms and school situations.
Keywords: Teachers -- Philippines -- Davao City -- Congresses; Teaching -- Philippines -- Davao City